The Use of Heuristic Reasoning in Christian Education - A Dan Kia (STAI Hubbulwathan Duri, 2023)
The grace of Christ needs to be on the agenda of preaching Christian Education in the current after-pandemic atmosphere. Students need clarity about themselves and why they must entrust their lives to the Lord Jesus. The contribution of Christian educators is to strive for them to grow in faith and become mature disciples of Christ later. The process of becoming a disciple of Christ, of course, is by paying attention to the cognitive workings of each student. And it becomes an essential part of Christian pedagogy so that teaching quality hits and succeeds. Heuristic reasoning is one of the proposed models because Christ himself used this reasoning with many people, including His disciples. This study aims to describe the definition and benefits of applying heuristic reasoning as a teaching method in Christian Education (hereafter, Pendidikan Agama Kristen/ PAK). This interview-based study utilized the perceptions of 20 PAK teachers in Indonesia discussing the benefits of heuristic reasoning at different levels of education and its implication in teaching Christian education. The findings revealed heuristics help teachers make quick decisions without being bogged down by irrelevant information. Thus, educators can leverage heuristics to encourage critical thinking, decision-making, and problem-solving skills among their students.